2020
DOI: 10.1080/14789949.2020.1820067
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Mental Health Problems and Violent Extremism

Abstract: A wide range of studies investigating the nature and determinants of radicalisation, and terrorist-related behaviour exist. These, in turn, have influenced theory, policy and practice in areas concerned with violent extremism prevention, disruption and management. As such interventions become more common, debates rage within mental health professions about the role mental health practitioners should play in countering violent extremism. This systematic review assesses the impact of mental health problems upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 108 publications
(102 reference statements)
7
61
0
3
Order By: Relevance
“…Indeed, it appears that Simi et al's hypothesis of identity discrepancies following failed role adjustments within the military, or after transition into civilian life, might hold some empirical value, since the majority (77,2 percent) of the sample were retired from military duty when they radicalized. In general, many theories of radicalization that strongly focus on grievances, 58 mental health issues, 59 or ostracism, 60 as the driving factors appear to help explain the significance of these variables among our group of far-right military background cases. Naturally, military service, especially when it involves deployment to an active combat situation, includes numerous intense physical and psychological risks and strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it appears that Simi et al's hypothesis of identity discrepancies following failed role adjustments within the military, or after transition into civilian life, might hold some empirical value, since the majority (77,2 percent) of the sample were retired from military duty when they radicalized. In general, many theories of radicalization that strongly focus on grievances, 58 mental health issues, 59 or ostracism, 60 as the driving factors appear to help explain the significance of these variables among our group of far-right military background cases. Naturally, military service, especially when it involves deployment to an active combat situation, includes numerous intense physical and psychological risks and strains.…”
Section: Discussionmentioning
confidence: 99%
“…44 Specifically, a landmark systematic literature review by Gill et al identified a wide array of mental health issues found among extremists and terrorists, among which trauma and substance abuse induced disorders are prevalent. 45 Especially relevant to the potential mental health impact of deployment is Post-Traumatic Stress Disorder (PTSD). 46 Recent research argued that this condition itself cannot be counted as a risk factor for radicalization, but interacts with other influences, and might facilitate that process once it has begun.…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of motivations, studies of members of organized terrorist groups or militant extremists suggest that most individuals do not have psychiatric disorders (Trimbur et al, 2021); however, mental illness does play a role in 'lone actors' who are not tied to a network or community (Gill et al, 2021;Silver et al, 2019). People who become radicalized may share common vulnerabilities that are intensified by events and mobilized by social forces.…”
Section: Social-psychological Dimensions Of Radicalization To Violencementioning
confidence: 99%
“…Finally, terrorism is often attributed to individual psychopathologies (Lankford, 2014;Laqueur, 2003) such as psychopathy (e.g., Cooper, 1978;Pearce, 1977;Post, 1987), and personality disorders (Johnson & Feldmann, 1992;Pearlstein, 1991). Yet, although often intuitive, the importance of psychopathology has been questioned (Gill et al, 2021).…”
Section: Risk Factors Predicting Terrorismmentioning
confidence: 99%